A cross‐cultural review and perspective on status striving. Issue 7 (19th July 2019) - Kim, Hee Young; Pettit, Nathan C.
Abstract: A significant body of research on the motives and pathways to attaining status has accumulated in the last few decades. At the same time, many of the commonly held assumptions and established findings in the status literature are drawn from research conducted in industrialized Western cultures. In this article, we review several fundamental differences between two widely studied cultures—Eastern and Western cultures—and propose that the core premises in the status literature map far more neatly onto what is known about Western cultures and less well onto what is known of Eastern cultures. More specifically, we examine cross‐cultural differences with respect to the meaning of status, motives underlying status pursuits, and the pathways that lead to status. We note how the reasons behind status pursuits may diverge among people from these two cultures, and how the behaviors that people employ when striving for status in Western cultures may not be effective in Eastern cultures. We conclude by proposing several avenues for future research.